Association of Circulating Vitamin D With Colorectal Cancer Depends on Vitamin D–Binding Protein Isoforms: A Pooled, Nested, Case-Control Study. Issue 1 (15th October 2019) - Gibbs, David Corley; Song, Mingyang; McCullough, Marjorie L; Um, Caroline Y; Bostick, Roberd M; Wu, Kana; Flanders, W Dana; Giovannucci, Edward; Jenab, Mazda; Brustad, Magritt; Tjønneland, Anne; Perez-Cornago, Aurora; et al.
Abstract: Background: Higher circulating 25-hydroxyvitamin-D [25(OH)D] concentrations are consistently inversely associated with colorectal cancer (CRC) risk in observational studies. However, it is unknown whether this association depends on the functional GC- rs4588*A (Thr436Lys) variant encoding the vitamin D–binding protein-2 (DBP2) isoform, which may affect vitamin D status and bioavailability. Methods: We analyzed data from 1710 incident CRC cases and 1649 incidence-density–matched controls nested within three prospective cohorts of mostly Caucasians. Study-specific incidence rate ratios (RRs) for associations of prediagnostic, season-standardized 25(OH)D concentrations according to DBP2 isoform with CRC were estimated using multivariable unconditional logistic regression and were pooled using fixed-effects models. All statistical significance tests were two-sided. Results: The odds of having 25(OH)D concentrations less than 50 nmol/L (considered insufficient by the Institute of Medicine) were 43% higher for each DBP2-encoding variant (rs4588*A) inherited (per DBP2 odds ratio [OR] = 1.43, 95% confidence interval [CI] = 1.27 to 1.62, P trend = 1.2 × 10 −8 ). The association of 25(OH)D concentrations with CRC risk differed by DBP2: 25(OH)D concentrations considered sufficient (≥ 50 nmol/L), relative to deficient (< 30 nmol/L), were associated with a 53% lower CRC risk among individuals with the DBP2 isoform (RR = 0.47, 95% CI = 0.33 to 0.67), but with a non–statistically significant 12% lower risk among individuals without it (RR = 0.88, 95% CI = 0.61 to 1.27) ( P heterogeneity = .01). Conclusions: Our results suggest that the 25(OH)D-CRC association may differ by DBP isoform, and those with a DBP2-encoding genotype linked to vitamin D insufficiency may particularly benefit from adequate 25(OH)D for CRC prevention.